LB005KIDNEY IMPLICATIONS OF THE INITIAL EGFR RESPONSE TO SGLT2 INHIBITION WITH EMPAGLIFLOZIN: THE 'EGFR DIP' IN EMPA-REG OUTCOME. (7th June 2020) - Kraus, Bettina J; Weir, Matthew; Bakris, George; Mattheus, Michaela; Cherney, David; Sattar, Naveed; Lambers Heerspink, Hiddo; Ritter, Ivana; Von Eynatten, Maximilian; Zinman, Bernard; Inzucchi, Silvio; Wanner, Christoph; et al.
Abstract: Background and Aims: Empagliflozin (EMPA) reduces cardiovascular and renal risk in patients with type 2 diabetes (T2D) and established cardiovascular disease (CVD). EMPA induces an initial 'dip' in estimated glomerular filtration rate (eGFR). Although considered to be of haemodynamic origin and largely reversible, this needs to be better understood. We investigated whether the initial eGFR dip after EMPA initiation was influenced by baseline characteristics and/or might have an impact on the EMPA-induced risk reduction in kidney outcomes. Method: In the EMPA-REG OUTCOME trial, patients with T2D and established CVD were treated (1:1:1) with EMPA 10 mg, 25 mg or placebo (PBO), in addition to standard of care. In this post hoc analysis, 6, 668 participants who received at least one dose of study drug and had an available eGFR value at both baseline and Week 4 were categorised by initial percentage eGFR change from baseline. A multivariate logistic regression model was used to identify which baseline characteristics are predictive of an initial eGFR dip >10% in EMPA-treated participants versus PBO. Across these predictive baseline factors, we investigated the occurrence of incident or worsening nephropathy, hard kidney outcomes (defined as doubling of serum creatinine with eGFR [MDRD] ≤45 ml/min/1.73 m2 or initiation of renal replacement therapy or death from renal disease), and kidney safety (narrow standardized MedDRA query acute renal failure). The impact of an eGFR dip >10% on the risk reduction with EMPA for incident or worsening nephropathy was assessed using Cox regression analysis adjusting for such eGFR dip. Results: In the EMPA-REG OUTCOME trial cohort, an initial eGFR dip of >10% from baseline at Week 4 occurred in more than twice as many participants on EMPA (28.3%) compared to PBO (13.4%). However, a more pronounced eGFR dip of >30% was uncommon, occurring in only 1.4% and 0.9%, respectively. Within the EMPA group, participants with an eGFR dip >10% were significantly older, had longer diabetes duration and showed a higher KDIGO (Kidney Disease: Improving Global Outcomes) risk category. Diuretic use and/or higher KDIGO risk category at baseline were predictive of an initial eGFR dip of >10% in EMPA vs. PBO. The average odds ratio [OR; 95% CI] for an eGFR dip >10% with EMPA was 2.7 [2.3–3.0]. In subgroups with a dipping odds ratio below vs. above that average, beneficial treatment effects with EMPA on incident or worsening nephropathy and the hard kidney outcome were consistent (panel A). Also, an eGFR dip >10% did not affect risk reduction for the primary kidney outcome (panel B). Acute renal failure rates were generally lower or similar in EMPA vs. PBO, regardless of baseline predictive factors for an eGFR dip. Conclusion: T2D patients with more advanced kidney disease and/or on diuretic therapy at baseline were more likely to have an initial eGFR dip >10% with EMPA. However, EMPA treatment appeared to be safe and was associated with improved kidney outcomes, regardless of these baseline predictive factors or an initial eGFR dip >10%.